Legal protection of distributors for wholesale seller in payment agreements with the tempo system review of consumer protection laws No. 8 year 1999 and syafi'i school (case study of outdoor goods distributor Iwak-P Malang) - Qoidatul Khusnah (Requisitoire Law Enforcement, 2022)
In doing business, the business actor already recognizes the relationship between all wholesale sellers and in the payment agreement made at the distributor of outdoor goods, Iwak-P carries out with a tempo system that must pay half the price in advance, even though the seller or wholesaler has been given a waiver, they are also given 1 week to pay half the price and then in this distributor agreement there are still those who don't pay and end up experiencing arrears of capital that they want to deposit to the factory, the distributor still needs to place an order to the factory in order to send goods to other wholesalers. The type of research used in this research is empirical with a qualitative approach. Data collection methods that researchers use are interviews, literature and documentation. The number of informants in this study were 2 people, namely distributors and wholesalers. From the results of interviews with informants, the researcher then analyzed based on the Consumer Protection Act No. 8 of 1999 and the Syafi'i School. The conclusion from this study, that the practice of agreements made by distributors with wholesalers does not fulfill achievements, in Consumer Protection no.8 of 1999 that the rights and obligations of business actors are not carried out in good faith there are debt arrears by wholesalers which result in distributors experiencing losses for not directly depositing it at the factory. According to the Syafi'i school, there is no problem with the debt-receivable agreement due to the tempo system, because as long as it is the will of the distributor, because what is meant in qardh is that the contract knows no time limit. That the distributor at the time owed the wholesale seller based on sincerity and without coercion.